Indonesian Society of Respirology Position Paper on Lung Cancer Control in Indonesia - Andarini, Sita; Santoso, Andintia Aisyah; Arfiansyah, Mochammad Aris; Syahruddin, Elisna; Zaini, Jamal; Putra, Andika Chandra; Kurniawan, Ferry Dwi; Ermayanti, Sabrina; Soeroso, Noni Novisari; Munir, Sri Melati; Infianto, Andreas; Setijadi, Ana Rima; Setyawan, Ungky Agus; Wulandari, Laksmi; Haryati, Haryati; Jasminarti, Ida Ayu; Hidayat, Moulid; Santoso, Arif (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Lung cancer is a major health concern in Indonesia due to its increasing prevalence, late-stage diagnosis, younger population, and high mortality. Addressing this issue requires nationwide implementation of comprehensive lung cancer control, which includes risk reduction and prevention strategies, focusing on tobacco control and air pollution mitigation. Screening with low-dose computed tomography (LDCT) and early detection in symptomatic patients, along with TB screening programs and all non-communicable diseases, is strongly recommended to enhance early case findings, treatment effectiveness, and overall patient outcomes. A multidisciplinary team (MDT) approach is important to ensure accurate diagnosis and comprehensive care. Moreover, the integration of palliative care at the early stages of advanced lung cancer is vital, focusing on symptom management and enhancing the quality of life for patients. While national guidelines are available for the diagnosis and treatment of lung cancer, significant disparities in healthcare access remain across Indonesia. Thus, it is essential to improve universal health coverage and referral systems to guarantee equal access to lung cancer care for patients at all levels through advocacy and ease of access.